School principals in Mexico : cases of leadership success - Torres Arcadia, Carmen Celina; Pesqueira Bustamante, Norma Guadalupe; Murakami, Elizabeth; Flores Kastanis, Eduardo (International research on school leadership., 2020)
This book was published in Spanish in 2016, and was initially compiled in memory of Eduardo Flores Kastanis, PhD, who pioneered and promoted the Proyecto Internacional de Directivos Exitosos (International Project of Successful School Principals) in Mexico. In the Mexico volume, Dr. Flores Kastanis is honored not only as a researcher and a prominent professor, but also as a visionary with a great interest in educational transformation and innovation in educational management. He dreamed of transforming the organizational structures prevailing in the educational system, which, as he used to say, coincided with teaching and management models in the industrial era. His vision was that schools as organizations need to develop learning-centered knowledge. He left a great legacy to those who believe that this dream is possible to benefit education in México. This book includes fourteen cases of successful principals, with a clear example that this dream can be a reality. This volume demonstrates how principals influence success in 14 elementary schools across Mexico. The cases show the importance of learning in an international school leadership context to address cultural, social, and academic needs of students in their families. Characteristics of successful principals are included, in order to exemplify contemporary practices, generate positive school climate, and the best possible development of children in diverse contexts.The cases presented in this book relate to challenging and vulnerable contexts or high-needs schools. Knowledge about successful school leadership in vulnerable contexts has been highly pursued in the U.S. and abroad, especially in countries where educational disparities relate to equity and social justice. The value of school principals merit visibility with a focus on the Americas.Especially in challenging contexts, school leadership is considered a determining factor in promoting the development of children. Nonetheless, there is much to learn about contemporary school leaders, who succeed in improving schools despite societal challenges. Challenges may include increasing socioeconomic restraints, high accountability demands, and reduced resources for public education. Of note, is that a formal preparation and assignment of principals is not equitably established in Mexico, generating a high need for leaders to be prepared for this important role. By highlighting best leadership practices, practitioners and scholars can reflect about United States and Mexico educational comparisons, and observe school improvement geared towards benefitting Latinx communities in both countries.